Repression of Jasmonate-Dependent Defenses by Shade Involves Differential Regulation of Protein Stability of MYC Transcription Factors and Their JAZ Repressors in Arabidopsis - Chico, José-Manuel (American Society of Plant Biologists, 2014)
Reduction of the red/far-red (R/FR) light ratio that occurs in dense canopies promotes plant growth to outcompete neighbors but has a repressive effect on jasmonate (JA)–dependent defenses. The molecular mechanism underlying this trade-off is not well understood. We found that the JA-related transcription factors MYC2, MYC3, and MYC4 are short-lived proteins degraded by the proteasome, and stabilized by JA and light, in Arabidopsis thaliana. Dark and CONSTITUTIVE PHOTOMORPHOGENIC1 destabilize MYC2, MYC3, and MYC4, whereas R and blue (B) lights stabilize them through the activation of the corresponding photoreceptors. Consistently, phytochrome B inactivation by monochromatic FR light or shade (FR-enriched light) destabilizes these three proteins and reduces their stabilization by JA. In contrast to MYCs, simulated shade conditions stabilize seven of their 10 JAZ repressors tested and reduce their degradation by JA. MYC2, MYC3, and MYC4 are required for JA-mediated defenses against the necrotrophic pathogen Botrytis cinerea and for the shade-triggered increased susceptibility, indicating that this negative effect of shade on defense is likely mediated by shade-triggered inactivation of MYC2, MYC3, and MYC4. The opposite regulation of protein stability of MYCs and JAZs by FR-enriched light help explain (on the molecular level) the long-standing observation that canopy shade represses JA-mediated defenses, facilitating reallocation of resources from defense to growth.